Does poverty negate the impact of social norms on cheating? - Suparee Boonmanunt; Agne Kajackaite; Stephan Meier (Games and Economic Behavior, 2020)
Cheating such as corruption and tax evasion is prevalent in the developing world; therefore, many interventions have been undertaken to reduce cheating in developing countries. Although some field evidence shows that poverty is correlated with cheating, the causal effect of poverty on cheating in the field and the effectiveness of interventions for financially constrained people remain an open question. We present results from a lab-in-the-field experiment with low-income rice farmers in Thailand (N = 568), in which we, first, investigate the causal effect of poverty on cheating and, second, test whether poverty affects the effectiveness of a social-norm intervention to reduce cheating. We show poverty itself does not affect willingness to cheat. However, although a social-norm-reminder intervention reduced cheating when the population was richer (after harvest), it had no effect when the population was poorer (before harvest). Our results suggest that the timing of interventions to change behavior might matter.
Keywords: C91; C93; D82; D91; 300; cheating; lying; poverty; social norms; interventions; lab-in-the-field experiment